ADAPTIVE TESTING IN THE CONTEXT OF USING ELECTRONIC LEARNING TOOLS: ESSENCE, DEVELOPMENT AND ASSESSMENT - Radkevych, Oleksandr (Professional Pedagogics, 2023)
The relevance of the article is determined by the appropriateness of using adaptive testing in education based on electronic learning tools, in particular Google Forms for accurate measurement of knowledge and skills of learners.Aim: to illuminate the general concept of adaptive testing of learners in the context of using electronic learning tools.Methods: literature analysis was aimed at a detailed study of scientific works of foreign and domestic researchers, articles, books and other sources of information related to the object of research - to clarify the current state of the problem, identify unresolved issues and determine directions for further research; case study - for analyzing a specific case, or a series of cases in the context of the study; formation of conclusions.Results: the significance of adaptive testing in the educational process, which adapts to the needs of each learner, is highlighted. Its advantages and disadvantages are disclosed. Varieties of adaptive testing are identified: linear, computer-based, and combined. The importance of adaptive testing using artificial intelligence is highlighted. The requirements for the preparation of adaptive tests are considered, in particular the importance of evaluation criteria and complexity parameters. The importance of feedback from students and the need to review tests to maintain their relevance and validity are emphasized. The general safety rules when working with Google Forms and the importance of automatic grading of student responses are characterized. The process of analyzing student responses and displaying test results is defined. The possibilities of integrating Google Forms with educational platforms are considered. The advantages and limitations of using Google Forms for adaptive testing in general secondary education institutions are emphasized.Conclusions: It is determined that adaptive testing is an important tool for deep analysis and creation of accurate complexity parameters of test questions. The need to implement feedback from students for continuous improvement of the testing process is emphasized. The importance of regular review and updating of tests to ensure their relevance is noted. Attention is drawn to taking into account the differentiation of questions by level of complexity, relevance to the learning context, and general educational goals.
Keywords: adaptive testing; Google Forms; feedback; evaluation criteria; automatic grading; general secondary education